ANALISIS STRATEGI PENGELOLAAN ANGGARAN KAS DALAM MENJAGA LIKUIDITAS DAN PROFITABILITAS PADA PT ABC - Affro, Salma; Tannar, Oryza (Media Mahardhika, 2026)
This study aims to analyze cash budget management strategies in an effort to maintain liquidity and profitability at PT ABC during the period 2022 to 2024. This study uses a qualitative descriptive approach using liquidity and profitability ratio analysis. The data sources for this study are financial position reports and income statements for the period 2022 to 2024. This study examines the company's cash budget based on secondary data (three-year financial reports) and primary data from interviews and observations of internal budget managers at PT ABC. The cash budget management strategy at PT ABC during the 2022–2024 period succeeded in maintaining the company's liquidity level, as indicated by an increase in the current ratio, cash ratio, and quick ratio. Although profitability ratios such as ROA, ROE, GPM, and NPM have declined, net profit has remained stable every year. This study provides practical implications for companies regarding the importance of structuring and adapting cash budgets. The analysis results show that good cash budget management not only helps companies maintain liquidity but also supports profit stability despite fluctuations in asset efficiency. There is a direct relationship between cash budget management strategies and the simultaneous stability of liquidity and profitability ratios in medium-sized companies. This differs from previous studies.